1997
DOI: 10.1111/j.1651-2227.1997.tb18336.x
|View full text |Cite
|
Sign up to set email alerts
|

The testis: the witness of the mating system, the site of mutation and the engine of desire

Abstract: There is now abundant evidence in a wide range of mammalian and non‐mammalian species to show that the relative size of the testis and the morphology of the spermatozoa are infallible predictors of the mating system. Species with the largest testis/body weight ratios and the best spermatozoa have a multi‐male or promiscuous mating system in which sperm competition operates. Judged by these criteria, men were not designed to be promiscuous. There is increasing evidence in humans to show that most spontaneous mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 19 publications
2
80
0
6
Order By: Relevance
“…Indeed, there are no traits that exhibit greater differences between the sexes than those tied directly to reproduction -the gonads and gametes. The male homologs of these traits (the testes and sperm) exhibit high metabolic activity (Ewing et al 1966, Short 1997, while their female counterparts (ovaries and ova) are relatively quiescent (Short 1997). Indeed, in vertebrates, the capacity of sperm to fertilise the ova depends primarily on their motility, powered by a small number of mitochondria packed within the sperm midpiece.…”
Section: Theory Linking the Mitochondria To Male Fertilitymentioning
confidence: 99%
“…Indeed, there are no traits that exhibit greater differences between the sexes than those tied directly to reproduction -the gonads and gametes. The male homologs of these traits (the testes and sperm) exhibit high metabolic activity (Ewing et al 1966, Short 1997, while their female counterparts (ovaries and ova) are relatively quiescent (Short 1997). Indeed, in vertebrates, the capacity of sperm to fertilise the ova depends primarily on their motility, powered by a small number of mitochondria packed within the sperm midpiece.…”
Section: Theory Linking the Mitochondria To Male Fertilitymentioning
confidence: 99%
“…Although it has been argued that homeothermy was responsible for the scrotal state (Werdelin and Nilsonne, 1999), among other things this does not tally with the testocondid status of birds. The idea that testis cooling may reduce sperm mutations was aired on the basis that recombinant repair by meiotic crossing-over is precluded by the heterogametic (XY) state of male mammals, unlike that of homogametic [ZZ] male birds (Short, 1997). Yet, not only does the testicondid situation occur without genetic penalty in some male mammals, but it is now evident that gene conversions occur between palindromic arms of the eutherian Y chromosome (Rozen et al, 2003).…”
Section: Sperm Capacitationmentioning
confidence: 99%
“…In statistically assessing a wide range of mammals, Freeman (1990) concluded that internal testes tend to be larger relative to body size, and that relative testis size declines according to the degree of descent. Since sperm production largely relates to the size of the testis (Moller, 1989;Short, 1997), the degree to which it is externalized could therefore represent a trade-off between sperm production and storage. In other words, optimizing sperm storage may enable a lower sperm production by the testis without compromising male This illustrates the discrete bald region that covers the cauda epididymidis, in contrast to the heavy fur that overlies both testes.…”
Section: Sperm Capacitationmentioning
confidence: 99%
“…When comparing prepubertal to adult testes, the fractional volume occupied by the seminiferous tubules increased from 81% to 89% in guinea pig and from 70% to 89% in cutia. According to Short (1997), the only way to increase the sperm production is by increasing the volume of seminiferous tubular tissue and testicular size, because the rate of sperm production per gram of testicular tissue is almost constant within the species. Zhengwel et al (1997) showed that the number of germinative cells is strongly related to testicular volume.…”
Section: Discussionmentioning
confidence: 99%